PENEGAKAN HUKUM TERHADAP PEMBAJAKAN DI LAUT MELALUI YURISDIKSI MAHKAMAH PIDANA INTERNASIONAL - Gunawan, Yordan (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
The international community, nowadays is facing the most serious problem of the piracy in the sea on a large scale than ever before. Todays piracy is destroying and disturbing the shipping industry worldwide with the modern way. The problem of piracy becomes increase day by day rather than to decrease. It is universally called as hostis humani generis. The piracy today is directed against victims from around the world, creates harms that are felt by the international community, and involves many of the same violation, as like as a murder and hostage-taking, that are used to commit the crimes within the jurisdiction of International Criminal Court (ICC). The main purpose of this paper is to describe the piracy in details which could be seen in some international laws concerning this problem as for UNCLOS 1982 and SUA Convention 1988. This paper also will elaborate how piracy could be called as a crime under international law, as well as the jurisdiction of the ICC. This permanent international judicial body is empowered to prosecute crimes of concern to the international community as a whole, in accordance with the Rome Statute 1998 and ICC is expected to fullfil the impunity as the biggest obstacle for countries to bring the pirates into the justice.